A meta-analysis to study the effects and relationships of various selenium sources and forms on production performance, antioxidant status and egg quality of laying hens - Yano, Aan Andri; Astuti, Dian; Respati, Adib Norma; Ningsih, Niati; Triswanto; Purnamayanti, Lailatul; Gao, Min; Rahman, Md Atikur; Abdel-Moneim, Abdel Moneim Eid; Elsadek, Mohamed Farouk; Abu Hassim, Hasliza; Faiz Md. Azmi, Amirul; et al. (John Wiley and Sons Ltd, 2025)
BACKGROUND: Nowadays, there is increasing interest in optimizing the beneficial effects on egg quality and production by investigating various levels and sources of Se. METHODS: Data of various forms, sources and levels of Se were analyzed using a meta-analysis approach in terms of their effects on production, antioxidant activity and egg Se deposition of laying hens by using 81 peer-reviewed publications. RESULTS: Overall, laying hens' performance and egg quality attributes were not affected by Se supplementation, except for minor changes in egg weight and eggshell thickness in response to higher Se levels in diets. Noticeable effects were found on antioxidant activities where organic Se outperformed the inorganic form. Strong linear relationships between Se levels in the diet and Se content of whole egg, egg yolk and egg albumen were found where Se in the form of selenomethionine (SM) exhibited a stronger relationship with Se content in whole egg (R2 = 0.954), egg yolk (R2 = 0.972) and egg albumen (R2 = 0.926) than other forms of organic Se and inorganic Se (sodium selenite). Also observed was a Se preferential deposition in egg yolk compared with egg albumen especially for SM, indicating a higher bioavailability and deposition rate of SM than other Se sources. CONCLUSION: Various forms of Se could be safely supplemented to diets at high doses of up to 5 mg kg−1 without adversely affecting hens' performance while enhancing antioxidant status. Supplementation with SM could be the most effective strategy to improve egg Se status among other forms of Se which may be beneficial for consumers.